From 'marginal to marginal': environmental justice under the Trump administration. Issue 2 (3rd April 2022) - Kohl, Ellen; Sullivan, Marianne; Chambers, Mark Milton; Cordner, Alissa; Sellers, Chris; Fredrickson, Leif; Ohayon, Jennifer Liss
ABSTRACT: How damaging was the Trump administration to environmental justice (EJ) efforts and policy? Since federal EJ oversight at the United States Environmental Protection Agency (EPA) is governed by executive order, rather than statute, approaches to it have varied by presidential administration. In this paper, we draw on interviews with current and recently retired EPA employees along with staffing and budget data, to examine how EJ has historically been supported and enacted within the agency, with a focus on identifying impacts of the Trump administration on EPA's EJ work. We find that while leadership support for EJ and emphasis across the agency have changed across presidential administrations, the EJ program has always held a marginal position in terms of allocation of resources and emphasis in regulatory decision-making. Starting from this position of long-term marginalization, EPA's EJ program was further marginalized by the Trump administration. Though EPA employees expressed divided opinions as to how consequential the Trump administration's actions were on enacting EJ internally, many thought that the administration's emphasis on deregulation had significant health consequences in EJ communities. We argue that the impacts of the Trump administration, like those of future administrations, must be assessed within a historical context.